Molecular and genetic characterization of lactose-metabolic genes of Streptococcus cremoris. - Inamine, J M (1986)
Lac+ plasmid DNA from Streptococcus cremoris H2 was subcloned with an Escherichia coli vector on a 3.5-kilobase-pair PstI-AvaI fragment. Genetic analysis of the cloned DNA was possible because linear Lac+ DNA fragments were productive in the S. sanguis transformation system. Complementation of S. sanguis Lac-mutants showed that the 3.5-kilobase-pair fragment included the structural gene for 6-phospho-beta-D-galactosidase and either enzyme II-lac or factor III-lac of the lactose-specific phosphoenolpyruvate-dependent phosphotransferase system. Expression of the S. cremoris-like 40,000-dalton 6-phospho-beta-D-galactosidase in S. sanguis Lac+ transformants, rather than the 52,000-dalton wild-type S. sanguis enzyme, demonstrated the occurrence of gene replacement and not gene repair. The evidence supports chromosomal integration as the mechanism by which S. sanguis Lac- recipients are converted to a Lac+ phenotype after transformation with Lac+ DNA. Southern blot data suggest that the Lac+ DNA does not reside on a transposon, but that integration always occurs within a specific HincII fragment of the recipient chromosome. Hybridization experiments demonstrate homology between the S. cremoris Lac+ DNA and cellular DNA from Lac+ strains of Streptococcus lactis, S. mutans, S. faecalis, and S. sanguis.